Interfirm cooperatives enabling organizational ambidexterity, a case study of the printing industry in Colombia. (29th May 2022) - Camargo Benavides, Andres Felipe; Ehrenhard, Michel; De Visser, Matthias; de Weerd‐Nederhof, Petra C.
Abstract: Research into organizational ambidexterity at the interorganizational level is limited, but it is even more scarce when considering emerging markets and alternative organizational forms such as the cooperative enterprise. We will attempt to fill these research gaps by offering in‐depth case studies of three interfirm cooperatives within the printing industry in Colombia. We analyze how interfirm cooperatives enable organizational ambidexterity in its small‐to‐medium‐sized enterprises (SMEs), and explore which factors are hindering ambidexterity. Our findings indicate that lower socioemotional wealth in SMEs undermines the need to invest in exploration. Additionally, cooperation within an interfirm cooperative appears to be entirely reliant on its component SMEs agreeing on the right balance of social and economic values. We conclude that, although the interfirm cooperative may play an important role in facilitating ambidexterity in emerging markets, transitioning from a primarily transactional role to a higher role as intermediator of ambidexterity poses significant challenges.